FDI Inspired Energy Consumption in Selected Emerging Markets: Does Financial Development Matter? - Kunofiwa Tsaurai (Comparative Economic Research. Central and Eastern Europe, 2018)
The study investigated the impact of the complementarity between foreign direct investment (FDI) and financial development on energy consumption in emerging markets. Although the relevance of the FDI-led energy consumption hypothesis is no longer contestable, the combined influence of FDI and financial development on energy consumption is not yet resolved. Random and fixed effects show that the interaction between outstanding domestic private debt securities and FDI had a significant positive influence on energy consumption whereas pooled ordinary least squares (OLS) noted that the interaction between FDI and outstanding domestic public debt securities positively and significantly affected energy consumption. The dynamic generalized methods of moments (GMM) shows that the interaction between (1) FDI and stock market capitalization and (2) FDI and stock market value traded had a significant negative influence on energy consumption. The study urges emerging markets to deepen the bond sector market in order to enhance FDI-led energy consumption.
Keywords: F21; E44; Q4; 330; energy consumption; FDI; financial development; emerging markets